Drying Kinetics and Combustion Characteristics of Carbonized Cashew Nut Shell Briquettes Under Open Sun, Passive and Active Solar Drying - ISHOLA, Sarafa; OLAOYE, Olusegun S.; ADEGBOLA, Adeyinka A.; OLUREMI, Isaac A.; AGBEDE, Oluseye O. (FUDMA Journal of Engineering and Technology, 2026)
This study investigated the influence of different drying methods (open sun, passive solar, and active solar drying) on the drying kinetics and combustion properties of carbonized cashew nut shell briquettes (CCNS-B). Cashew nut shells were carbonized at 250 °C for 3 h, pulverized, and densified using cassava starch as a binder at a pressure of 5 MPa. The briquettes were then subjected to controlled drying conditions, and their drying behaviour was evaluated using moisture ratio, drying rate, and effective moisture diffusivity. In addition, thin-layer drying models were applied to describe the drying kinetics, while proximate and ultimate analyses were used to assess fuel quality. The results showed that active solar drying achieved the shortest drying time (900 min) compared to passive solar (1080 min) and open sun drying (1260 min). Drying occurred entirely in the falling-rate period, indicating diffusion-controlled moisture transport. Effective moisture diffusivity increased from 4.50 × 10⁻⁹ m²/s (open sun) to 9.49 × 10⁻⁹ m²/s (active solar). Among twelve evaluated thin-layer models, the Midilli-Kucuk model best described the open sun and active solar drying, while the logarithmic model best depicted the kinetics of the passive solar drying of the briquettes (R² ≥ 0.990). Proximate analysis revealed improved fuel quality under active solar drying, with lower moisture (2.01%), reduced volatile matter (51.04%), and higher fixed carbon (38.62%). Ultimate analysis showed minimal variation in elemental composition across drying methods. The higher heating value ranged from 25.18 to 25.76 MJ/kg, with the highest value observed in active solar drying. Overall, active solar drying produced superior briquette quality and is recommended for efficient biomass fuel processing.